Understanding the effect of sex on energy requirements of hair sheep - C.J.L. Herbster; A.P. Oliveira; A.S. Brito Neto; E.S. Justino; I.A.M.A. Teixeira; J.A.G. Azevedo; S.A. Santos; L.P. Silva; M.I. Marcondes; R.L. Oliveira; L.R. Bezerra; E.S. Pereira (Animal, 2024)
Differences and/or similarities in the influence of sex class for hair sheep requirements remain inconclusive. Knowledge of energy requirements allows well-formulated diets to be provided which is crucial for improving animal production. We aimed to determine the effect of sex class on the net energy requirements of growing hair sheep in a multi-study approach. We used a data set composed of individual measurements of 382 hair sheep (299 non-castrated and 83 castrated males) from 11 studies that used the methodology of comparative slaughter. Net energy requirements for maintenance (NEm) were obtained by the regression between heat production and metabolizable energy intake. The metabolizable energy requirements for maintenance (MEm) were calculated by the iterative method, and the efficiency of use of metabolizable energy for maintenance (km) was obtained by NEm divided by MEm. The net energy requirements for gain (NEg) were estimated from retained energy (RE) against empty BW gain (EBWG). The efficiency of energy use for weight gain (kg) was obtained from the relationship between RE and the energy metabolizable intake for gain, removing the intercept. There was an effect of sex on NEg and two equations were generated: NEg (MJ/day) = 1.040 (±0.04055) × EBW0.75 × EBWG0.8767(±0.03293) and NEg (MJ/day) = 1.040 (±0.04055) × EBW0.75 × EBWG0.8300(±0.03468) (R2 = 0.86; MSE = 0.0037; AIC = −468.0) for non-castrated and castrated males, respectively. Sex class did not affect kg (P > 0.05) and one kg was generated (0.29). Sex did not affect kprotein (P = 0.14) and kfat (P = 0.32), assuming an average deposition efficiency of 0.27 for protein and 0.78 for fat. The NEm and MEm did not differ (P > 0.05) between sex classes, with a value of 0.272 and 0.427 MJ/kg0.75 EBW per day, respectively. The km observed was 0.64. In conclusion, non-castrated and castrated male hair sheep have similar maintenance energy requirements although energy requirements for gain differed among them. The Committees overestimate the gain and maintenance requirements for hair sheep. Therefore, the equations generated in this study are recommended.